Le risque tsunamique au Maroc : modélisation et évaluation au moyen d'un premier jeu d'indicateurs d'exposition du littoral atlantique - Samira Mellas; Frédéric Leone; Rachid Omira; Monique Gherardi; Maria-Ana Baptista; Bendahhou Zourarah; Mathieu Péroche; Émilie Lagahé (Physio-Géo)
This paper seeks to estimate the exposure of the Atlantic coast of Morocco to tsunami risk. A methodological approach and a first set of tsunami risk indicators are presented. The proposed approach is based upon a coupling of tsunami numerical modeling with coastal land use geo-referenced databases. Tsunami numerical modeling is performed for a 1755-like earthquake scenario allowing the prediction of travel times, wave heights and flooding areas on 67 communes (local administrative units). While, the obtained main geo-indicators allow to compare the tsunami risk for population, and industrial/urban areas at a regional scale along Moroccan Atlantic coast. These results are aggregated over several territorial units and are expressed in absolute or relative values to provide the widest range of maps to decision makers. The exposure to tsunami risk is high along the Rabat-El Jadida mid-Atlantic urban corridor. These results give an insight on the estimation of tsunami risk in Morocco, which needs to be improved and updated in a prevention and awareness approach.